Profiling and bioinformatic analysis reveal differential microRNA expression in the left and right kidneys in normal mice. Issue 4 (14th November 2019) - Gao, Yuanxu; Yang, Weili; Jin, Ling; Xue, Lixiang; Yang, Jichun; Cui, Qinghua
Abstract : Physiological and pathophysiological differences exist between the left and right kidneys; however, the molecular bases for these differences remain unknown. Since miRNAs are involved in kidney function and the development of kidney diseases, we examined their differential expression through miRNA profiling of the left and right kidneys of normal mice. We find that 36 miRNAs exhibit higher expression, whereas 22 miRNAs show lower expression in the left than the right kidneys in mice under physiological condition. Ten miRNAs were further examined by quantitative PCR assays, and four of them with high expression level were confirmed by Northern blot. Through bioinformatic analysis, we dissected the function and network of the differentially expressed miRNAs, providing insights into the physiological and pathophysiological differences between the left and the right kidneys. Abstract :